Trans-Ureteral Ureterolithotripsy of Ureteral Calculi:Which is the Best; Pneumatic or Holmium Laser Technique? - Razzaghi, Mohammad Reza; Razi, Abdollah; Mazloomfard, Mohammad Mohsen; Mokhtarpour, Hooman; Javanmard, Babak; Mohammadi, Reza (Journal of Lasers in Medical Sciences, 2011)
INTRODUCTION: Our aim was compare of two types of lithotripter include holmium: YAG laser and pneumatic one in transurethral ureterolithotripsy (TUL) for the management of ureteral calculi ≥1 cm. METHODS: 112 patients with ureteral calculi more than 1 cm were selected in randomized order for pneumatic or holmium: YAG laser transurethral ureterolithotripsy (56 patients in each group). Ultrasonography and intravenous urography were performed for all patients before surgery. Complete clearance and success was defined as the absence of any fragments on post operation KUB and ultrasonography images. RESULTS: Success rate was 85.7% in pneumatic group and 100% in holmium: YAG laser group (p =0.003). Stone migration up in the pelvicalyceal system was observed only in 8 cases of pneumatic group. No statically differences were observed in terms of patient’s age, hospital stay, and complications between two groups. CONCLUSION: According to our experience, for ureteral stone larger than 1 Cm treatment with ureteroscopy and laser lithotripsy is a preferring approach with favorable operation time and hospital admission, and no more significant complication.